AKR1B8 deficiency drives severe DSS-induced acute colitis through invasion of luminal bacteria and activation of innate immunity - Deng, Qiulin; Yao, Yichen; Yang, Jing; Khoshaba, Ramina; Shen, Yi; Wang, Xin; Cao, Deliang (Frontiers in Immunology, 2022)
Background: Dysfunction of intestinal epithelial cells (IECs) promotes inflammatory bowel disease (IBD) and associated colorectal cancer (CRC). AKR1B8 deficiency impairs the IEC barrier function, leading to susceptibility to chronic colitis induced by dextran sulfate sodium (DSS), yet it remains unclear how acute colitic response is in AKR1B8 deficient mice. Methods: AKR1B8 knockout (KO) and littermate wild type mice were exposed to oral 1.5% DSS in drinking water for 6 days. Disease activity index and histopathological inflammation scores by H&E staining were calculated for colitic severity; permeability was assessed by fluorescein isothiocyanate dextran (FITC-Dextran) probes and bacterial invasion and transmission were detected by in situ hybridization in mucosa or by culture in blood agar plates. Immunofluorescent staining and flow cytometry were applied for immune cell quantification. Toll-like receptor 4 (TLR4) and target gene expression was analyzed by Western blotting and qRT-PCR. Results: The results showed AKR1B8 KO mice developed severe acute colitis at a low dose (1.5%) of DSS in drinking water compared to wild type controls. In AKR1B8 KO mice, FITC-dextran was penetrated easily and luminal bacteria invaded to the surface of IEC layer on day 3, and excessive bacteria translocated into the colonic mucosa, mesenteric lymph nodes (MLNs) and liver on day 6, which was much mild in wild type mice. Hyper-infiltration of neutrophils and basophils occurred in AKR1B8 KO mice, and monocytes in spleen and macrophages in colonic mucosa increased markedly compared to wild type mice. TLR4 signaling in colonic epithelial cells of AKR1B8 KO mice was activated to promote great IL-1β and IL-6 expression compared to wild type mice. Conclusion: AKR1B8 deficiency in IECs drives severe acute colitis induced by DSS at a low dose through activation of the innate immunity, being a novel pathogenic factor of colitis.